An ethnobotanical study on wild edible plants in Taishan County, Guangdong, China - Zhang, Shuangyu; He, Chunmei; Su, Lingye; Wang, Hongfeng; Lin, Jieyu; Li, Yuling (Frontiers in Sustainable Food Systems, 2025)
Globally, wild edible plants (WEPs) play a critical role in sustaining livelihoods and preserving cultural heritage. This study investigates traditional knowledge of WEPs in Taishan County, Guangdong Province of China, through market surveys, semi-structured interviews (n = 162), and participant observation, with the primary objective of sustainable utilization of WEPs and safeguarding their cultural significance. Finally, 131 WEPs belonging to 59 families were identified, which are mainly used as tea substitutes, wild vegetables, and spices. We analyzed the diversity of consumed WEPs, documented the utilized plant parts and preparation methods, selected 8 culturally significant species [Portulaca oleracea L., Houttuynia cordata Thunb., Plantago asiatica L., Centella asiatica (L.) Urb., Amaranthus spinosus L., Perilla frutescens (L.) Britton, Hypericum japonicum Thunb. ex Murray, and Eleutherococcus trifoliatus (L.) S. Y. Hu] via the Cultural Food Significance Index (CFSI) analysis, and provided the sustainable utilization strategies. These plants are deeply embedded in local traditions, including medicinal herbal teas, nutritious Cantonese-style soups, and bitter-tasting tonic dishes, embodying the “Food as Medicine” philosophy. However, this knowledge is now predominantly held by older generations, and threatened by rapid urbanization and youth disengagement. Future research should prioritize strategies to conserve cultural and ecological diversity while incorporating WEPs into contemporary food systems.